Strategi Dakwah Syekh Ghazali - Dindin Solahudin (Faculty of Da'wah and Communication, UIN Sunan Gunung Djati, Bandung, 2011)
Amid this postmodern era, dakwah has to undergo a sort of paradigm shift at a strategic level in line with rapid development of information and communication technology. In terms of this, Syekh Ghazali promotes three strategies. First, dakwah needs to focus and be oriented to universal tenets of Islam. In so doing, it might neglect such trivial affairs and particular aspects of Islam as the so-called furû’iyyah and juz’iyyât. Second, dakwah needs to be moderate in nature without being trapped in any extremism, neither fundamentalist right nor liberalist left. Third, dakwah need to be tapped through multimedia in such a way that it would reach people of any segments at any social levels.